Giant and dwarf - China's two faces in wind energy innovation - Carsten Gandenberger (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2017)
A functional analysis of the TIS for wind energy in China has revealed a great disparity in performance with respect to different functions of innovation. A particular strength of the Chinese TIS is the rapid diffusion of wind power equipment which presupposes the development of domestic production capabilities, the successful adoption of existing technology, the creation of markets and legitimacy as well as the ability to mobilize financial resources. Furthermore, Chinese universities and research institutes have quickly expanded their capabilities in the area of basic research. In contrast, China's performance in the area of applied research is mixed. Although the growth in the number of transnational and domestic wind energy patents indicates that China is now among the most inventive countries in the world, a more detailed analysis suggests that inventions are less focused on the most relevant technology subfields and that Chinese firms are reluctant to engage in innovation. The most prominent drawback of the centralized planning approach in China are governance deficits relating to the integration of wind energy into China's electricity grid as well as to the lack of complementary infrastructure for energy transmission and storage. These deficits result in high curtailment rates, low incentives for quality oriented innovation, and a low overall efficiency of wind energy in China.
urn:nbn:de:0011-n-4562190
Keywords: 330; Technological Innovation System; Functions of Innovation; China; Wind Energy